2012
DOI: 10.3174/ajnr.a3271
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Computerized Language Lateralization Index from fMRI by a Group of Clinical Neuroradiologists

Abstract: BACKGROUND AND PURPOSE:Deriving accurate language lateralization from fMRI studies in the clinical context can be difficult, with 10%-20% incorrect conclusions. Most interpretations are qualitative, performed by neuroimaging experts. Quantitative lateralization has been widely described but with little implementation in the clinical setting and is disadvantaged by the use of arbitrary threshold techniques. We investigated the application and utility of a nonthreshold CLI, in a clinical setting, as applied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Studies comparing quantitative with qualitative assessment of language lateralization have shown that visual inspection by an experienced rater is reliable for presurgical assessment of language lateralization. [29][30][31] This qualitative approach provided a clinically applicable assessment of the cerebrocellebellar relationship in patients with tumor.…”
Section: 23mentioning
confidence: 99%
“…Studies comparing quantitative with qualitative assessment of language lateralization have shown that visual inspection by an experienced rater is reliable for presurgical assessment of language lateralization. [29][30][31] This qualitative approach provided a clinically applicable assessment of the cerebrocellebellar relationship in patients with tumor.…”
Section: 23mentioning
confidence: 99%
“…Our approach rather aims at standardizing visual interpretation, making it less dependent on rater experience but still applicable in the clinical context, where inferences must be drawn from individual patient's dataset, even at the cost of suboptimal data quality [51]. This is in accordance with studies showing that visual inspection by an experienced rater is a reliable and valuable method to validate and interpret fMRI in a clinical routine setting [26,[52][53][54][55][56][57][58][59]. Gaillard et al [54] compared visual assessment of fMRI with quantitative methods such as the LI and found comparable results.…”
Section: Discussionmentioning
confidence: 85%
“…These might include information about the patient's compliance with the task, movement-associated signal changes (24) and whether a sufficient amount of data was collected (39). Of note, subjective ratings of data quality have been shown to vary strongly between different evaluators (40). Therefore, it seems imperative to advance the development of automated data quality assessments and the understanding of how data quality and measures of lateralisation interact.…”
Section: Discussionmentioning
confidence: 99%